Efficient preparation of the inclined La1-xCaxMnO3 films with excellent light-induced transverse thermoelectric performance based on MOCVD process. (February 2023) - Chen, Xi; Tao, Bowan; Zhao, Ruipeng; Yang, Kai; Li, Zhenzhe; Xie, Tian; Zhong, Yao; Zhang, Tong; Xia, Yudong
Abstract: The efficient preparation of inclined La1-x Cax MnO3 (LCMO) films with excellent light-induced transverse thermoelectric (LITT) performance on c -axis miscut 12° SrTiO3 single crystal substrates is achieved based on the home-designed metal-organic chemical vapor deposition (MOCVD) system. The LCMO films with the thickness of 300 nm are prepared in 1 min, and the preparation efficiency reaches 300 nm/min. Under the radiation of 248 nm pulsed laser with the duration time of 28 ns, the voltage signal of LCMO films shows high sensitivity of 3.13 V/mJ and fast response time of 28 ns, superior to the LITT performance of the reported LCMO under the irradiation of pulsed laser with similar wavelength and duration time. The improvement of LITT performance originates from good electrical conductivity and biaxial texture. Additionally, under the radiation of 900 nm continuous laser, the obvious response voltages can be detected in the LCMO films, and the voltage amplitudes increase linearly with increasing laser power densities. These results demonstrate the application potential of the light detectors composed of LCMO films based on the efficient preparation of MOCVD, and may provide a good prospect for developing low-cost and high-performance light detectors based on the LITT effect. Highlights: Efficient preparation of inclined La1-x Cax MnO3 films is achieved based on MOCVD. The inclined La1-x Cax MnO3 films show outstanding LITT performance. Good conductivity and biaxial texture are the keys to enhance LITT effect.